(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2019)
Environmental monitoring of air quality is becoming increasingly important. The main part of cars has more than 10 years of age. Thereby running of these cars is more than 100 thousand kilometers and it means that ecological characteristics of most vehicles are equal to or exceed regulatory. The analysis of exhaust emissions toxicity showed that the vehicles operated in Kokshetau has emissions that are close to the maximum permissible. The use of additives and new fuels, traffic improving, car driving optimization and the development of alternative car designs will contribute to the normalization of air pollution of cities. The system of state control over air is intended to be the guarantor in the implementation of these measures to improve environmental safety of vehicles. Key words: environmental monitoring, air quality condition, regulation of air quality, means of controlling toxic gases in the atmosphere, pollution, analysis, emissions, vehicle, operation of the engine.